2015
DOI: 10.3892/mmr.2015.3170
|View full text |Cite
|
Sign up to set email alerts
|

α-lipoic acid protects against cerebral ischemia/reperfusion-induced injury in rats

Abstract: Abstract. It is well established that the brain is sensitive to ischemia/reperfusion (I/R)-induced injury. α-lipoic acid (LA), a free radical scavenger and antioxidant, has a neuroprotective effect against cerebral I/R-induced injury, however, the underlying mechanisms remain to be elucidated. Therefore, the present study was undertaken to evaluate whether LA was able to protect against cerebral I/R-induced injury and to examine the potential mechanisms. The neuroprotective effects of LA were investigated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Studies have confirmed that T-AOC regulation can protect neuronal damage in CIRI (Deng et al, 2015;Lin et al, 2015;Kryl'skii et al, 2019). α-lipoic acid exerted its neuroprotective effects through reversing the levels of oxidative parameters, including malondialdehyde (MDA), nitric oxide (NO), T-AOC, and SOD to their normal state in rat brains following CIRI (Deng et al, 2015). Lin et al found that neuronal damage in the hippocampal CA1 area was significantly reduced after cerebral ischemia/reperfusion in SOD transgenic mice (Lin et al, 2015;.…”
Section: Enzymatic and Non-enzymatic Antioxidant Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have confirmed that T-AOC regulation can protect neuronal damage in CIRI (Deng et al, 2015;Lin et al, 2015;Kryl'skii et al, 2019). α-lipoic acid exerted its neuroprotective effects through reversing the levels of oxidative parameters, including malondialdehyde (MDA), nitric oxide (NO), T-AOC, and SOD to their normal state in rat brains following CIRI (Deng et al, 2015). Lin et al found that neuronal damage in the hippocampal CA1 area was significantly reduced after cerebral ischemia/reperfusion in SOD transgenic mice (Lin et al, 2015;.…”
Section: Enzymatic and Non-enzymatic Antioxidant Systemsmentioning
confidence: 95%
“…Non-enzymatic systems include glutathione (GSH), vitamin A, vitamin C, Vitamin E, and carotenoids (Kryl'skii et al, 2019). Studies have confirmed that T-AOC regulation can protect neuronal damage in CIRI (Deng et al, 2015;Lin et al, 2015;Kryl'skii et al, 2019). α-lipoic acid exerted its neuroprotective effects through reversing the levels of oxidative parameters, including malondialdehyde (MDA), nitric oxide (NO), T-AOC, and SOD to their normal state in rat brains following CIRI (Deng et al, 2015).…”
Section: Enzymatic and Non-enzymatic Antioxidant Systemsmentioning
confidence: 99%
“…MAPK signaling is certainly diverse, and its functions can differ depending on the cell type and context [61], however, this pro-survival function is in line with the vast majority of studies describing pMAPK signaling in neurons [44]. It is also in line with increased MAPK signaling acting as a protective mechanism against hypoxic insults [57,62,63].…”
Section: Discussionmentioning
confidence: 70%
“…Male Sprague-Dawley rats weighing 260-300 g (n=36; 1.5 years old) were obtained from the Experimental Animal Centre of Zhangqiu People's Hospital (Jinan, China) and were allowed free access to laboratory chow and tap water in day-night quarters at 25˚C with 50-60% humidity and a 12-h light/dark cycle. The experiment was approved by the Committee on Animal Experiments of Zhangqiu People's Hospital (14). All rats were randomly divided into the following three experimental groups (n=12 per group): Sham, sham-operated rats pretreated intraperitoneally with normal saline for 3 days; cerebral IRI model, cerebral IRI model rats pretreated intraperitoneally with normal saline for 3 days; and pentoxifylline treatment group, cerebral IRI model rats pretreated daily with 46.7 mg/kg pentoxifylline (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) intraperitoneally for 3 days.…”
Section: Methodsmentioning
confidence: 99%